Multi-state models of transitions in depression and anxiety symptom severity and cardiovascular events in patients with coronary heart disease - Meyer, Michelle L.; Mons, Ute; Brenner, Hermann (PLOS ONE, 2019)
Objective Patients with coronary heart disease (CHD) commonly suffer from depression and anxiety, yet transitions of symptom severity and cardiovascular events (CVE) over time are not well characterized. Methods We included 997 patients with stable CHD from a prospective cohort study. We estimated 5- and 10-year transition probabilities of depression and anxiety symptom severity levels and fatal- and non-fatal adverse CVE. Depression and anxiety symptoms were measured with the Hospital Anxiety and Depression Scale 5 times over 13 years and categorized as no, mild, or moderate/severe symptoms. Using multi-state modeling, we calculated 5- and 10-year transition probabilities for depression and anxiety symptom severity and CVE and calculated transition intensity ratios for factors associated with symptom severity progression and regression. Results At 5 years, only approximately half of participants with moderate or severe symptom severity at baseline transitioned to no symptom severity. Patients with low physical activity (<1x/week or never) had a higher probability of worse symptom severity after 5 and 10 years and a higher probability of a CVE after 5 and 10 years regardless of their depression status at baseline compared to higher physical activity groups. Higher body mass index, <10 years of education, and lower physical activity were associated with depression symptom progression; female and lower physical activity were associated with anxiety symptom progression. Conclusions Patients with CHD had a consistent burden of depression and anxiety symptoms. Secondary prevention strategies should target depression and anxiety and include a physical activity component.
Gesehen am 25.04.2019